Linguistic imagelogy: research potential - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article examines the issue of changing of scientific paradigms and strategies of analysis, the formation of new research areas in modern times. Current statements of Western epistemology regarding the transformation of the scientific worldview from traditional spheres of knowledge to functional, communicative, syncretic, typical for the information age are commented. The logic of Jacqueline Rus's argument according to the radical changes in modern science, commensurate with the development of humanity and societies, is clarified.The essence of intellectual processes in current linguistics is analyzed, when a strong interest in the functional capabilities of the language has been formed since the end of the 19th century, instead of the traditional attention to the system and structural description of the language. The functional resource of language is interpreted in the article as an immanent property revealed in stylistic modifications of genres and texts.At the same time, the stylistic polyphony of texts, cognition of their communicative harmony with the purpose and objectivity of communication give rise to new research directions in linguistics – media linguistics, political and business linguistics, linguistic imagelogy, etc.Linguistic imageology as a special research field of scientific interests in philology is still being formed as a systematic direction. Syncretic in essence, linguoimageology determines the main parameters of the discipline – object, subject of analysis, strategies, tactics, methods of language activity, specific methods of text analysis, etc. in discussions and ambiguous formulations.The article presents a link for the first publication in this field – "Linguistic imageology: dictionary of terms and concepts" as a model and a possible criterion for systematic linguoimageology research. The edition conceptually forms the main categories and concepts of the direction, presents scientific definitions based on the researched locus of the functional and communicative language resource of the information world correlated with other directions of humanities.
Keywords: media linguistics, linguistic imagelogy, integral links of linguistic imagelogy, strategies of linguistic imagelogy, tactics of linguistic imagelogy, information age, Jacqueline Russ.